The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-27087-9
|View full text |Cite
|
Sign up to set email alerts
|

Wireless control of cellular function by activation of a novel protein responsive to electromagnetic fields

Abstract: The Kryptopterus bicirrhis (glass catfish) is known to respond to electromagnetic fields (EMF). Here we tested its avoidance behavior in response to static and alternating magnetic fields stimulation. Using expression cloning we identified an electromagnetic perceptive gene (EPG) from the K. bicirrhis encoding a protein that responds to EMF. This EPG gene was cloned and expressed in mammalian cells, neuronal cultures and in rat’s brain. Immunohistochemistry showed that the expression of EPG is confined to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 59 publications
3
67
0
Order By: Relevance
“…The HEK293T cells were transfected with a pcDNA3.1 vector construct containing the EPG gene under the CMV promoter pcDNA3.1-EPG+GFP [32] ( Figure 1A). Figure 1B shows the schematic drawing of the biological circuit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HEK293T cells were transfected with a pcDNA3.1 vector construct containing the EPG gene under the CMV promoter pcDNA3.1-EPG+GFP [32] ( Figure 1A). Figure 1B shows the schematic drawing of the biological circuit.…”
Section: Resultsmentioning
confidence: 99%
“…The measured responded cells were described as a numeric value at a given time point. Responding cells were determined using the following equation (Equation 1) [32]:…”
Section: Cell Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one of the drawbacks of this technology is the requirement to deliver the light directly into the target neural population. Here we tested if neuromodulation via the magnetic sensitive protein EPG, which provides cell and temporal specificity while being activated remotely via non-invasive electromagnetic fields 53 , can be utilized to restore cortical excitability and achieve similar sensorimotor outcomes compared to rTMS. The results demonstrate that daily magnetic activation of EPG improved sensory, motor, and an overall well-being of the injured rats in a battery of behavioral tests that were performed up to 4 weeks after the EPG treatment ended.…”
Section: Discussionmentioning
confidence: 99%
“…One of these technologies, magnetic manipulation by the electromagnetic preceptive gene (EPG), allows non-invasive and cell-specific neuromodulation using external magnetic fields. EPG is a protein that is sensitive to electromagnetic fields which was recently identified in the fish Kryptopterus bicirrhis 43 . Recent work had demonstrated that calcium imaging in mammalian cells and cultured neurons expressing EPG activated remotely by magnetic fields led to increases in intracellular calcium concentrations, indicative of cellular excitability.…”
Section: Introductionmentioning
confidence: 99%